DIREITO AO DESENVOLVIMENTO: UMA ABORDAGEM A PARTIR DA PERSPECTIVA DE AMARTYA SEN (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The subject outlined in this article is the right to development, having as objective understand it from the concept of the Amartya Sen, mainly within the proposal of development as freedom. Through a deductive study based on a literature review, the study denote that the right to development can't be seen only in economic terms, being related, much more, to the substantive freedoms granted to individuals, that it is harmonized with the notion of human rights.